Rapid development of clone‐specific, high‐performing perfusion media from established feed supplements. (11th November 2019) - Mayrhofer, Patrick; Reinhart, David; Castan, Andreas; Kunert, Renate
Abstract: Perfusion cultivation of recombinant CHO cells is of substantial interest to the biopharmaceutical industry. This is due to increased space–time‐yields (STYs) and a short residence time of the recombinant protein in the bioreactor. Economic processes rely on cultivation media supporting rapid growth in the exponential phase and high protein production in the stationary phase at minimal media consumption rates. To develop clone‐specific, high‐performing perfusion media we present a straightforward and rapid two‐step approach combining commercially available basal media and feed supplements using design‐of‐experiment. First, the best performing feed supplements are selected in batch cultures. Then, the mixing ratio of selected feed supplements is optimized in small‐scale semicontinuous perfusion cultures. The final media formulation is supported by statistical response surface modeling of a set of cultivation experiments with blended media formulations. Two best performing novel media blends were finally applied to perfusion bioreactor verification runs to reach 200 × 10 6 c/ml within 2 weeks at minimum cell‐specific perfusion rates as low as 10–30 pL/c/d. Obtained STYs of 0.4–1.2 g/L/d represent a 10‐fold increase compared to batch cultures. This general workflow is universally applicable to any perfusion platform combining a specific cell line, basal medium, and established feed solutions.